2020
DOI: 10.1021/acs.est.0c04473
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Trends of Anionic, Zwitterionic, and Cationic PFASs at an AFFF-Impacted Site

Abstract: Soil and groundwater from an aqueous film-forming foam (AFFF)-impacted site were sampled at high resolution (n = 105 for soil, n = 58 for groundwater) and analyzed for an extensive list of anionic, zwitterionic, and cationic poly- and perfluoroalkyl substances (PFASs). Spatial trends for perfluoroalkyl acids and many precursors enabled a better understanding of PFAS composition, transport, and transformation. All PFASs without analytical standards were semi-quantified. Summed PFAS and individual PFAS concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
161
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(189 citation statements)
references
References 53 publications
16
161
0
Order By: Relevance
“…In general, sites with more retention will likely be more amenable to using MNA to manage PFAS in the subsurface. Two examples of this general PFAS MNA retention framework are presented herein; first, a hypothetical PFAS site with a PFAS mass distribution based in part on partitioning data from Brusseau (2018), and second, an actual site described by Adamson et al (2020) and Nickerson et al (2021). The scientific basis for PFAS MNA detailed in this paper was used to develop potential guidelines for implementing PFAS MNA, which are presented in a companion paper ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, sites with more retention will likely be more amenable to using MNA to manage PFAS in the subsurface. Two examples of this general PFAS MNA retention framework are presented herein; first, a hypothetical PFAS site with a PFAS mass distribution based in part on partitioning data from Brusseau (2018), and second, an actual site described by Adamson et al (2020) and Nickerson et al (2021). The scientific basis for PFAS MNA detailed in this paper was used to develop potential guidelines for implementing PFAS MNA, which are presented in a companion paper ).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include hydrophobic and electrostatic interactions, which are a function of pH, ionic strength, organic carbon content, the charge of soil particles, chain lengths, and charge of the functional group of the PFAS (Nguyen et al 2020). The relative importance of these processes has been documented at PFAS field sites (Weber et al 2017;Adamson et al 2020;Nickerson et al 2021). For example, a field-scale evaluation of a former fire training area where aqueous film-forming foam (AFFF) had been released showed that zwitterionic and cationic precursors were strongly retained within the source area relative to PFAAs due to preferential sorption characteristics (Adamson et al 2020;Nickerson et al 2021).…”
Section: Partitioning/retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Branched and linear isomers will have different physical and chemical properties (water solubility, sorption, transport behavior, and bioaccumulation potentials) and, hence, are expected to show different fate and transport behavior (Kärrman et al, 2011). The isomer Environmental sources, chemistry, fate, and transport of PFAS-Environmental Toxicology and Chemistry, 2021;40:3234-3260 profiles present at the source of contamination will change and redistribute after a certain distance from the source, and in addition, the transformation of different precursor isomers may be different (Adamson et al, 2020;Anderson et al, 2016;Guelfo & Higgins, 2013;Liu, Zhong, et al, 2019;Nickerson et al, 2021). Therefore, measuring PFAS at a distance from the source may show different isomer profiles compared with the source, resulting in misinterpretation of sources.…”
Section: Isomer Profiles and Ratios Of Chain Lengthsmentioning
confidence: 99%